The mission of God unlocking the Bible's grand narrative - Wright, Christopher J. H. 1947- (Downers Grove, Il IVP Academic, 2006)
Contents: The Bible and mission -- The God of mission -- The people of mission -- The arena of mission. Includes bibliographical references and indexes.
Keywords: God (Christianity) -- will; Missions -- Theory; Mission of the church